Promotional effect of WOx in Pt-WOx/AlPO4-5 catalyzed deoxygenation of fatty acids - Janampelli, Sagar; Darbha, Srinivas (ChemistrySelect, 2017)
WOx promoted Pt/AlPO4-5 catalysts with varying Pt and W contents were prepared by wet-impregnation method and characterized. Catalysts with Pt to W weight ratio of 1: 2 exhibited higher catalytic performance than the other compositions in deoxygenation of oleic acid (OA). WOx enhanced significantly the catalytic activity of Pt and enabled quantitative conversion of OA to linear alkanes (predominantly C-18/C-17) at a temperature as low as 280 degrees C. It changed the reaction pathway from decarbonylation/ decarboxylation (DCO for Pt/AlPO4-5) to hydrodeoxygenation (HDO for Pt-WOx/AlPO4-5). It affected the particle size and redox behaviour of Pt. The enhanced H-spill over (by 14.8%) and presence of strong acid sites (300 - 500 degrees C) are the cause for the high activity of Pt-WOx/AlPO4-5 catalysts even at lower temperatures. Partially reduced WOx activates OA and leads to the HDO product (C-18). In the absence of WOx, Lewis acid sites of the support activate OA through the C=O group and Pt facilitates C-C cleavage and formation of DCO product (C-17).
Keywords: biofuels; Deoxygenation; Fatty acids; Green Diesel; Hydrocarbons

Selective and reusable Pt-WO x /Al 2 O 3 catalyst for deoxygenation of fatty acids and their esters to diesel-range hydrocarbons - Janampelli, Sagar; Srinivas, Darbha (Catalysis Today, 2017)
Tungsten oxide promoted platinum catalysts (Pt-WOx/Al2O3) of varying composition were prepared by wet impregnation method and reduced in hydrogen atmosphere. X-ray powder diffraction and photoelectron spectroscopy revealed that Pt is completely reduced to metallic state while tungsten is in +6 and +5 oxidation state. Pt crystallite and particle sizes increased (from 1.2 to 1.4 nm and 2.5 to 3 nm, respectively) in presence of WOx (CO-chemisorption and transmission electron microscopy). Tungsten addition augmented strong acid sites. It enhanced significantly the catalytic activity of Pt/Al2O3 in deoxygenation of fatty acids and their methyl esters. Tungsten altered the reaction pathway from decarbonylation/decarboxylation to hydrodeoxygenation. A catalyst with 4 wt% Pt and 8 wt% W exhibited high catalytic performance. Complete conversion of oleic acid and octadecane product selectivity in the range 67.1 − 80.8% was obtained. Pt-WOx/Al2O3 is a stable and reusable fatty acid deoxygenation catalyst.
Keywords: biofuels; Deoxygenation; Diesel-range hydrocarbons; Fatty acids; Pt catalyst

Hydrodeoxygenation of vegetable oils and fatty acids over different group VIII metal catalysts for producing biofuels - Janampelli, Sagar; Darbha, Srinivas (Catalysis Surveys From Asia, 2019)
Energy security and environment protection are two important aspects of sustainable development. Biofuels are renewable and carbon neutral. They are suitable replacement for conventional fossil derived transport fuels. Their use leads to sustainable development. Among several technological options, catalytic hydrodeoxygenation of vegetable oils leading to diesel-range hydrocarbons is the most attractive approach for producing biofuels. The green diesel, thus produced, could be blended with petro-diesel or used as standalone fuel in the conventional diesel engines. Our research group has been active in developing efficient solid catalysts for hydroprocessing of vegetable oils. This account presents some of our efforts using supported group VIII metals and the importance of electronic contact between metal and support on the catalytic activity and hydrodeoxygenation selectivity in hydroprocessing of vegetable oils.
Keywords: biofuels; Catalysis over group VIII metals; Deoxygenation; Hydroprocessing; Renewable diesel